Effects of long-term development and schooling expansion on the decline in homicide rates: Mexico from 1950 to 2005 - Zepeda Gil, Raúl (Journal of crime and justice, 2023)
Based on a recently published historical crime database that shows an unequivocal reduction of homicides in Mexico from the 1950s up until 2005, this paper aims to examine the effect of development policies on homicide reduction in 20th century Mexico. This research presents a panel regression of homicide rates in all 32 Mexican states from 1950 to 2005. Our research shows that the increase in schooling years in Mexico is correlated with the decline in homicide rates. This decline happened despite inverse pressure from social disorganisation caused by unequal economic growth and youth bulges during the period examined. Consequently, the paper shows that sustained development policies can be a pacifying mechanism in a country that has experienced accelerated urban growth and other structural problems associated with crime since the beginning of the century.